2007
DOI: 10.1016/j.expneurol.2007.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Loss of enteric dopaminergic neurons and associated changes in colon motility in an MPTP mouse model of Parkinson's disease

Abstract: Gastrointestinal (GI) dysfunction is the most common non-motor symptom of Parkinson's disease (PD). Symptoms of GI dysmotility include early satiety and nausea from delayed gastric emptying, bloating from poor small bowel coordination, and constipation and defecatory dysfunction from impaired colonic transit. Understanding the pathophysiology and treatment of these symptoms in PD patients has been hampered by the lack of investigation into GI symptoms and pathology in PD animal models. We report that the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
199
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(214 citation statements)
references
References 36 publications
11
199
3
1
Order By: Relevance
“…Overall, available data indicate either unchanged [2] or increased numbers of myenteric nitrergic neurons in the MPTP model of PD [10]. In our hands, rats lesioned with 6-OHDA showed a significant reduction in the percentage of myenteric neurons expressing nNOS in the distal ileum and proximal colon, while the total number of neurons was unchanged.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…Overall, available data indicate either unchanged [2] or increased numbers of myenteric nitrergic neurons in the MPTP model of PD [10]. In our hands, rats lesioned with 6-OHDA showed a significant reduction in the percentage of myenteric neurons expressing nNOS in the distal ileum and proximal colon, while the total number of neurons was unchanged.…”
mentioning
confidence: 45%
“…However, MPTP does not cause parkinsonism in rats (unlike primates and mice) [19], thus limiting the value of these observations. Anderson et al [2] reported a 40% reduction of dopamine neurons in the ENS of mice receiving intraperitoneal MPTP administration, without loss of cholinergic or nitrergic neurons. Recently, Tian et al [28] reported increased expression of TH and DAT in the GI tract of rats bearing bilateral lesions of the SNc obtained by stereotaxic injection of 6-hydroxydopamine (6-OHDA), a neurotoxin with selective toxicity for dopaminergic neurons [30].…”
mentioning
confidence: 99%
“…Additionally, the MPTP primate model has been indispensable in the development and testing of novel PD therapeutics as well as in studies examining side-effects of current PD therapies, such as dyskinesias in response to levodopa (49). Furthermore, recent data reporting gastrointestinal dysfunction in the MPTP mouse model (2,70) support the notion that MPTP-treated mice may be an appropriate model in which to study extranigral PD pathophysiology.…”
Section: Mptp Metabolism and Mitochondrial Mechanisms Of Neurotoxicitymentioning
confidence: 99%
“…Thus, we could exclude the role of neither central nor peripheral dopaminergic system in the beneficial effect of D2 agonists on the colonic lesion. Moreover, the data on duodenal ulceration indicated that dopamine-related drugs affect experimental duodenal ulcers both by peripheral and central actions [15][16][17]. Furthermore the importance of central dopamine in intestinal mucosal integrity was confirmed by Ray et al [16].…”
mentioning
confidence: 97%